Actualization of the Principles of Open Government in the Administration of Population Services in Bekasi Regency, West Java Province (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study aims to describe the actualization of Open Government principles in the implementation of population administration services and to analyze the efforts of the Bekasi Regency Government in overcoming various inhibiting factors in the application of Open Government values. A total of 14 informants were selected from various sectors, includingovernment officials, community members, and civil society organizations concerned with public service improvement in Bekasi Regency. Using a qualitative approach supported by in- depth interviews, field observation, and document analysis, this study identifies several key barriers: limited digital infrastructure, low digital literacy among citizens, weak public participation mechanisms, slow response to complaints, insufficient bureaucratic capacity, and fragmented service innovation. Findings reveal that the Bekasi Government has introduced adaptive and collaborative strategies such as mobile service outreach (jemput bola), community-based digital literacy programs, participatory forums like BOTRAM, designated complaint response officers, service excellence training for civil servants, and integration of services into the Smart City ecosystem. Innovations such as SIDEPI and the “Bekasi Nyambung Bae” app have become essential tools in strengthening accountability, transparency, and public engagement. Although structural and cultural challenges remain, the implementation of Open Government in Bekasi demonstrates a progressive trajectory, particularly through approaches rooted in co-creation and data-driven governance. This study recommends strengthening institutional frameworks, developing multi-stakeholder partnership guidelines, and conducting participatory monitoring and evaluation to ensure the sustainability of inclusive and open public service transformation.